Haplotype structure defines effects of common DPYD variants c.85T > C (rs1801265) and c.496A > G (rs2297595) on dihydropyrimidine dehydrogenase activity: Implication for 5‐fluorouracil toxicity. Issue 8 (30th March 2021) - Hamzic, Seid; Schärer, Dominic; Offer, Steven M.; Meulendijks, Didier; Nakas, Christos; Diasio, Robert B.; Fontana, Stefano; Wehrli, Marc; Schürch, Stefan; Amstutz, Ursula; Largiadèr, Carlo R.
Abstract : Aims: The aim of this study was to identify risk variants and haplotypes that impair dihydropyrimidine dehydrogenase (DPD) activity and are, therefore, candidate risk variants for severe toxicity to 5‐fluorouracil (5‐FU) chemotherapy. Methods: Plasma dihydrouracil/uracil (UH2 /U) ratios were measured as a population marker for DPD activity in a total of 1382 subjects from 4 independent studies. Genotype and haplotype correlations with UH2 /U ratios were assessed. Results: Significantly lower UH2 /U ratios (p anova < 2 × 10 −16 ) were observed in carriers of the 4 well‐studied 5‐FU toxicity risk variants with mean differences (MD) of −43.7% for DPYD c.1905 + 1G > A (rs3918290), −46.0% for DPYD c.1679T > G (rs55886062), −37.1%, for DPYD c.2846A > T (rs67376798), and −13.2% for DPYD c.1129‐5923C > G (rs75017182). An additional variant, DPYD c.496A > G (rs2297595), was also associated with lower UH2 /U ratios ( P < .0001, MD: −12.6%). A haplotype analysis was performed for variants in linkage disequilibrium with c.496A > G, which consisted of the common variant c.85T > C (rs1801265) and the risk variant c.1129‐5923C > G. Both haplotypes carrying c.496A > G were associated with decreased UH2 /U ratios (H3, P = .003, MD: −9.6%; H5, P = .002, MD: −16.9%). A haplotype carrying only the variant c.85T > C (H2) was associated with elevated ratios ( P = .004, MD: +8.6%). Conclusions: Based on our data, DPYD ‐c.496A > G is a strong candidate risk allele for 5‐FU toxicity. Our data suggest that DPYD ‐c.85T > C might be protective; however, the deleterious impacts of the linked alleles c.496A > G and c.1129‐5923C > G likely limit this effect in patients. The possible protective effect of c.85T > C and linkage disequilibrium with c.496A > G and c.1129‐5923C > G may have hampered prior association studies and should be considered in future clinical studies.